PENDIDIKAN KRITIS BERDIMENSI IDEOLOGIS KULTURAL - PUTERA SEMADI, ANAK AGUNG GDE (Widya Accarya, 2018)
ABSTRACTÂ Â  Â Â Â Â Â Â Â Â  In an effort to develop a critical education, the concept of education needs to be formulated as a process of cultural dimension / humanization process. The process of education can not be separated from human life in order to create cultural and cultural heritage (cultural creation and cultural transmission) to the young generation. Through the process of critical education, human beings are able to develop various potentials or creativity, taste, intention, and work that become the core of cultural process, because culture in the essential concept of education can be formulated as "The shared product of human learning". The main functions and targets of the paradigm to develop critical education are self-awareness, also known as critical awareness, and develop the main method of learning by emphasizing the principle of critical dialogical domination. Thus, the core process of critical education is not just the transfer of science / information, but is a psychological process or cultural practice towards awareness / self-liberation of learners.Â Keywords: Critical education, critical awareness, Dialogical-critical.Â Â AbstrakÂ Â Dalam upaya mengembangkan pendidikan kritis, maka konsep pendidikan perlu dirumuskan sebagai proses berdimensi kultural/proses humanisasi. Proses pendidikan tidak bisa dipisahkan dengan kehidupan manusia dalam rangka penciptaan budaya sekaligus pewarisannya (cultural creation and cultural transmission) kepada generasi muda. Melalui proses pendidikan kritis manusia mampu mengembangkan berbagai potensi atau daya cipta, rasa, karsa, dan karya yang menjadi inti proses budaya, karena budaya dalam konsep esensial pendidikan dapatÂ  dirumuskan sebagai â??The shared product of human learningâ?. Â Fungsi serta sasaran utama paradigma mengembangkan pendidikan kritis adalah upaya penyadaran diri, atau disebut pula dengan istilah kesadaran kritis, serta mengembangkan metode utama pembelajarannya dengan menekankan prinsip dominasi dialogis kritis. Jadi, inti proses pendidikan kritis bukanlah sekadar transfer ilmu/informasi, melainkan merupakan proses kejiwaan atau praktik kebudayaan menuju penyadaran/pembebasan diri peserta didik.Â Â Â Â Â Â  Kata kunci: Â Pendidikan kritis, Kesadaran kritis, Dialogis-kritis.